Crystallization and preliminary X-ray analysis of the YjgF/YER057c/UK114-family protein ST0811 from Sulfolobus tokodaii strain 7 - Miyakawa, Takuya (International Union of Crystallography, 2005)
ST0811 from Sulfolobus tokodaii strain 7, a member of the YjgF/YER057c/UK114 protein family, was crystallized by the sitting-drop vapour-diffusion method using PEG 10 000 as precipitant. The crystals diffracted X-rays to beyond 2.0 Å resolution using an in-house rotating-anode generator. The crystals belonged to the rhombohedral space group R3, with hexagonal unit-cell parameters a = b = 55.0, c = 223.2 Å. The crystals contained two molecules in the asymmetric unit (V (M) = 2.3 Å(3) Da(−1)) and had a solvent content of 47%.